Serum Magnesium Levels and Outcomes in Patients With Acute Spontaneous Intracerebral Hemorrhage. Issue 8 (13th April 2018) - Goyal, Nitin; Tsivgoulis, Georgios; Malhotra, Konark; Houck, Alexander L.; Khorchid, Yasser M.; Pandhi, Abhi; Inoa, Violiza; Alsherbini, Khalid; Alexandrov, Andrei V.; Arthur, Adam S.; Elijovich, Lucas; Chang, Jason J.
Abstract : Background: Magnesium (Mg) has potential hemostatic properties. We sought to investigate the potential association of serum Mg levels (at baseline and at 48 hours) with outcomes in patients with acute spontaneous intracerebral hemorrhage (ICH). Methods and Results: We reviewed data on all patients with spontaneous ICH with available Mg levels at baseline, over a 5‐year period. Clinical and radiological outcome measures included initial hematoma volume, admission National Institutes of Health Stroke Scale and ICH scores, in‐hospital mortality, favorable functional outcome (modified Rankin Scale scores, 0–1), and functional independence (modified Rankin Scale scores, 0–2) at discharge. Our study population consisted of 299 patients with ICH (mean age, 61±13 years; mean admission serum Mg, 1.8±0.3 mg/dL). Increasing admission Mg levels strongly correlated with lower admission National Institutes of Health Stroke Scale score (Spearman's r, −0.141; P =0.015), lower ICH score (Spearman's r, −0.153; P =0.009), and lower initial hematoma volume (Spearman's r, −0.153; P =0.012). Higher admission Mg levels were documented in patients with favorable functional outcome (1.9±0.3 versus 1.8±0.3 mg/dL; P =0.025) and functional independence (1.9±0.3 versus 1.8±0.3 mg/dL; P =0.022) at discharge. No association between serum Mg levels at 48 hours and any of the outcome variables was detected. In multiple linear regression analyses, a 0.1‐mg/dL increase in admission serum Mg was independently and negatively associated with the cubed root of hematoma volume at admission (regression coefficient, −0.020; 95% confidence interval, −0.040 to −0.000; P =0.049) and admission ICH score (regression coefficient, −0.053; 95% confidence interval, −0.102 to −0.005; P =0.032). Conclusions: Higher admission Mg levels were independently related to lower admission hematoma volume and lower admission ICH score in patients with acute spontaneous ICH.